In vitro evaluation of Ciprofloxacin Hydrochloride - Jaman, M; Chowdhury, AA; Rana, AA; Masum, SM; Ferdous, T; Rashid, MA; Karim, MM (Bangladesh Journal of Scientific and Industrial Research, 2015)
The in vitro evaluation of the physical characteristics of the pharmaceutical products ensures their quality as well as bioavailability and impart optimum therapeutic activity. Ciprofloxacin HCl, a widely used antibiotic to treat different types of bacterial infections, was chosen for this in vitro comparative study of different pharmaceutical company. The present study compared the content uniformity, weight variation, hardness, friability, thickness, diameter, disintegration and dissolution ability of five brands of ciprofloxacin HCl tablets marketed in Bangladesh to confirm whether they follow USP guidelines. All five brands of ciprofloxacin HCl tested meet the specification of the USP for content uniformity, weight variation, hardness, friability, thickness, diameter, disintegration and dissolution. The amount of active ciprofloxacin HCl varies from 244.46 mg to 248.46 mg among the products. The average hardness and friability of the products varies 73.9 N to 77.6 N and 0.013% to 0.031%, respectively. All the brands had shown disintegration time 5 to 8 minutes while they showed 80 to 95 % release of active ingredient within 30 minutes in dissolution testing. This may confirm the absorption of the drug from gastrointestinal tract for optimum therapeutic effect. Bangladesh J. Sci. Ind. Res. 50(4), 251-256, 2015